A Critical Analysis of the Book History and Social Theory - Maryam Eskafi Noghani; Gholamreza Sedigh Ouraee (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The purpose of this article is to evaluate the book “History and Social Theory”, translated by Gholamreza Jamshidiha. A general introduction of the work and a brief summary of it is presented after introducing and reviewing the necessity and background in this area. In the next section, formal, content, methodological, and translation evaluation is done. In this article, the original and translated text have been compared together, and its strengths and weaknesses have been extracted. The results showed that this book has many positive characteristics. The content of the book is compatible with basic assumptions because logically, the author has shown that history is part of sociology and sociology is part of the social sciences, so it can be concluded, like the author, that history is also part of the social sciences and is not inconsistent with Islamic values and religious principles. In terms of the volume of materials, information and knowledge transmitted, students and beginners unfamiliar with these sciences can make a lot of historical use of this book. Therefore, this book can be suggested as a source of tuition and utilization of its reliable resources for undergraduate and postgraduate students in the fields of sociology and history. The existence of more than 600 valuable historical and sociological sources in the bibliography is another very valuable point in this book. Also, the smooth and short translation of the heavy text and the main thaqil (regardless of its objection) is another strength of this book. However, the book does not match the latest headlines approved by the Ministry of Science, Research and Technology as the main book in the teaching of academic courses and is educational assistance book. The lack of result at the end of each chapter keeps the reader confused. Logical coherence is very weak in the content of each chapter and between the contents of different seasons. Eliminating some of the bugs in translation, editorial and editorial defects can add to the richness of work. Intra-modal corrections, especially for reader’s easier access to resources and to the day-to-day source of work, are fundamental issues that hope to be corrected in the next edition.